HUBUNGAN ANTARA BODY IMAGE DAN KEPERCAYAAN DIRI DENGAN KOMUNIKASI INTERPERSONAL REMAJA PEREMPUAN DI SMP ISLAM SUNAN GUNUNG JATI TULUNGAGUNG - Raras Amalia Cantika Siwi (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2024)
The objectives of this study include: 1) to determine the relation between body image and self-confidence with interpersonal communication in female adolescents SMP Islam Sunan Gunung Jati Tulungagung, 2) to find out the relation between body image with the interpersonal communication of female adolescent at SMP Islam Sunan Gunung Jati Tulungagung, and 3) to determine the relation between self-confidence with the interpersonal communication of female adolescent at SMP Islam Sunan Gunung Jati Tulungagung, 4) to to determine the relation between body image with self-confidence of female adolescent at SMP Islam Sunan Gunung Jati Tulungagung. The method used is a correlation quantitative research. The sample were female adolescent class VIII and IX with an age range of 13-15 years at SMP Islam Sunan Gunung Jati Tulungagung which has 195 students. The results showed that 1)there is a positif and not significant relation between body image and self-confidence with female adolescent interpersonal communication, 2) there is no relation between body image and female adolescent interpersonal communication, 3) there is a positif and significant relation between self-confidence and interpersonal communication of female adolescents, 4) there is a positif and significant relation beetwen body image with self-confidenceof female adolescents.